A Model of Germinal Matrix Hemorrhage in Preterm Rat Pups - Jinnai, Masako; Koning, Gabriella; Singh-Mallah, Gagandeep; Jonsdotter, Andrea; Leverin, Anna-Lena; Svedin, Pernilla; Nair, Syam; Takeda, Satoru; Wang, Xiaoyang; Mallard, Carina; Ek, Carl Joakim; Rocha-Ferreira, Eridan; et al. (Frontiers in Cellular Neuroscience, 2020)
Germinal matrix hemorrhage (GMH) is a serious complication in extremely preterm infants associated with neurological deficits and mortality. The purpose of the present study was to develop and characterize a grade III and IV GMH model in postnatal day 5 (P5) rats, the equivalent of preterm human brain maturation. P5 Wistar rats were exposed to unilateral GMH through intracranial injection into the striatum close to the germinal matrix with 0.1U, 0.2U or 0.3U of collagenase VII. During 10 days following GMH induction, motor functions and body weight were assessed and brain tissue collected at P16. Animals were tested for anxiety, motor coordination and motor asymmetry on P22-26 and P36-40. Using immunohistochemical staining and neuropathological scoring we found that a collagenase dose of 0.3 U induced GMH. Neuropathological assessment revealed that the brain injury in the collagenase group was characterized by dilation of the ipsilateral ventricle combined with mild to severe cellular necrosis as well as mild to moderate atrophy at the levels of striatum and subcortical white matter, and to a lesser extent, hippocampus and cortex. Within 0.5 h post-collagenase injection there was clear bleeding at the site of injury, with progressive increase in iron and infiltration of neutrophils in the first 24 h, together with focal microglia activation. By P16, blood was no longer observed, although significant grey and white matter brain infarction persisted. Astrogliosis was also detected at this time-point. Animals exposed to GMH performed worse than controls in the negative geotaxis test and also opened their eyes with latency compared to control animals. At P40, GMH rats spent more time in the centre of open field box and moved at higher speed compared to the controls, and continued to show ipsilateral injury in striatum and subcortical white matter. We have established a P5 rat model of collagenase-induced GMH for the study of preterm brain injury. Our results show that P5 rat pups exposed to GMH develop moderate brain injury affecting both grey and white matter associated with delayed eye opening and abnormal motor functions. These animals develop hyperactivity and show reduced anxiety in the juvenile stage.